GAMIANI, OR TWO NIGHTS OF EXCESS BY ALFRED DE MUSSET: CONSTRUCTION OF SUBJECTIVITY IN FRENCH “BLACK” - Andrey V. Golubkov (Studia Litterarum)
This essay examines Gamiani, or Two Nights of Excess, erotic novel by Alfred de Musset This essay examines Gamiani, or Two Nights of Excess, erotic novel by Alfred de Musset written at the beginning of the 1830s and widely popular in France until up to the 1920s. When writing the novel that belongs to the tradition of “black Romanticism,” de Musset was heavily drawing on the French tradition of libertinage, de Sade’s work in particular. However, he substantially revised and transformed its aesthetical and philosophical premises. The novel describing various sexual perversities of the main character, Gamiani, adheres to the aesthetical principles of Romanticism that cultivated geniality but also marginality seen as the symptom of exceptionalism. The character’s lesbian affairs may be interpreted in terms of the urge for the infinite lust, or Romantic “abyss.” These motifs became developed in Baudelaire’s The Flowers of Evil, especially in the poem “Lesbians.”